Исследование измерительной части цифровых устройств релейной защиты - Андреев М. В. Михаил Владимирович; Рубан Н. Ю. Николай Юрьевич; Суворов А. А. Алексей Александрович; Уфа Р. А. Руслан Александрович (2017, 2017)
Заглавие с экрана